Road Performance of Mica Powder Modified Asphalt Mixture - Chao FENG; Huiming BAO; Huan BAO; Wei ZHAN; Shi YAN (Kuangchan zonghe liyong)
This is an article in the field of ceramics and composites. In order to investigate the basic road performance of mica powder modified asphalt mixture, modified asphalt with 0%, 3%, 5%, 7%, 9%, and 11% content was prepared. Through rotational viscosity test, penetration test and Fourier infrared spectroscopy test, the performance of mica powder modified asphalt was analyzed. AC-20 mica powder modified asphalt mixture was prepared to explore its road performance and the influence law of mica powder dimension content on asphalt mixture road performance was determined by grey correlation analysis. The test results show that the addition of mica powder can reduce the temperature sensitivity of the asphalt, and the addition of mica powder to the asphalt only causes physical blending. As the content of mica powder increases, the improvement effect of mica powder on asphalt pavement performance first increases and then decreases. When the content of mica powder is 7%, the road performance of mica powder modified asphalt mixture reaches the best. The grey correlation analysis shows that the influence degrees of mica powder dosage on road performance indicators are high temperature stability > moisture stability > low temperature crack resistance．